2022
DOI: 10.1155/2022/9215685
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect of Butylphthalide Combined with Rt-PA Intravenous Thrombolysis in the Treatment of Acute Cerebral Infarction

Abstract: Objective. To assess the clinical effect of butylphthalide combined with rt-PA intravenous thrombolysis in the treatment of acute cerebral infarction (ACI). Methods. Totally, 312 acute cerebral infarction patients were included in this research. Those in the group for experiment received butylphthalide (25 mg QD) combined with rt-PA intravenous thrombolysis (0.9 mg/kg QD), while the control group received rt-PA intravenous ( P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Edaravone is a brain protective agent, and its active ingredient is N-acetylaspartic acid, which can effectively scavenge free radicals, inhibit lipid peroxidation and prevent nerve cells, vascular endothelial cells and brain cells from oxidative damage. Benphthalein soft capsule combined with edaravone in patients with cerebral infarction can enhance its protective effect on cerebral ischemia, effectively improve blood flow and microcirculation in ischemic brain area, and reduce brain edema, thus improving the curative effect [3]. Benphthalein soft capsule is a new anti-cerebral infarction drug, which has a good protective effect on mitochondria in brain tissue, can improve blood flow, energy metabolism and microcirculation in brain tissue, and can effectively inhibit cell apoptosis in brain tissue, which has a good therapeutic effect in brain tissue and can well control the volume of cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Edaravone is a brain protective agent, and its active ingredient is N-acetylaspartic acid, which can effectively scavenge free radicals, inhibit lipid peroxidation and prevent nerve cells, vascular endothelial cells and brain cells from oxidative damage. Benphthalein soft capsule combined with edaravone in patients with cerebral infarction can enhance its protective effect on cerebral ischemia, effectively improve blood flow and microcirculation in ischemic brain area, and reduce brain edema, thus improving the curative effect [3]. Benphthalein soft capsule is a new anti-cerebral infarction drug, which has a good protective effect on mitochondria in brain tissue, can improve blood flow, energy metabolism and microcirculation in brain tissue, and can effectively inhibit cell apoptosis in brain tissue, which has a good therapeutic effect in brain tissue and can well control the volume of cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%